In vivo MRI visualization of growth and morphology in the orthotopic xenotrasplantation U87 glioblastoma mouse SCID model - E. L. Zavjalov (Vavilovskij Žurnal Genetiki i Selekcii, 2015)
Glioblastoma multiforme (GBM) is the most common and lethal type of brain cancer with the average lifespan of patients about 9–12 months. The study of tumor formation and the evaluation of new therapies for GBM require accurate and reproducible experimental brain tumor animal models. In this study we used MRI for investigation of tumor morphology and growth dynamic in an orthopic xenotransplantation immunodeficient mouse model (SCID mouse line). Comparison of T1- and T2-weighed MRI scans preformed with a high-field MRI scanner (Bruker, BioSpec, 11,7 T) revealed insufficient tumor/normal tissue T1-contrast because of high longitudinal magnetization of the magnetic field in our scanner. Intravenous injection of paramagnetic manganese oxide (MnO) nanoparticles dramatically increased the tumor/normal tissue contrast in T1-weigthed MRI scans. The study of glioblastoma growth with T2-weighed images showed that a significant tumor development began not earlier than 3 weeks after cell culture intracranial injection and then the tumor grew exponentially. Thus, we developed a protocol of the characterization of glioblastoma U87 growth and morphology by T1- and T2-weighed and MnO-enhanced MRI in the orthopic xenotransplantation mouse model. The results demonstrate that this SCID model may be used as an in vivo preclinical model to test the efficacy and putative side effects of novel anticancer therapies.